The rate of stable crack growth (SCG) in automotive steels sheets - Ľ. Ambriško; M. Cehlár; D. Marasová (Metalurgija, 2017)
The main aim of this paper is determining the stable crack growth (SCG) rate for automotive steel sheets. The SCG was monitored using the non-contact videoextensometry technique. CT (Compact Tension) specimens of three steel grades were loaded by eccentric tension under two loading conditions. The SCG characteristics including rate depend on steel grade, on the rolling direction as well as on the loading rate. Linear relation between the SCG rate and δR-curve slope was determined.